1999
DOI: 10.1292/jvms.61.1161
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Marek’s Disease Virus Serotype 2 Genes Homologous to the Glycoprotein B (UL27), ICP18.5 (UL28) and Major DNA-Binding Protein (UL29) Genes of Herpes Simplex Virus Type 1

Abstract: ABSTRACT. We determined the nucleotide sequence of non-pathogenic Marek's disease virus serotype 2 (MDV2) strain HPRS24 glycoprotein B (gB) (UL27), ICP18.5 (UL28) and major DNA-binding protein (MDBP) (UL29) genes homologous to herpes simplex virus type 1 (HSV-1). The sequence data revealed that important motives in the proteins are conserved in MDV2 ICP18.5 and MDBP, however the sequence of viral DNA replication origin which exists in the regions between the UL29 and UL30 genes of other alphaherpesviruses was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…cDNA sequencing has revealed that the v-LIP transcript is made up of two exons; a signal sequence is conferred from a very short first exon and the catalytic domain is encoded by the much longer second exon. This pattern is conserved in the close homolog present in MDV-2 HPRS-24 (22). Remarkably, aside from the MDV-2 homolog, the closest homologs to v-LIP are ORFs from several avian and fowl adenoviruses (GenBank accession nos.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…cDNA sequencing has revealed that the v-LIP transcript is made up of two exons; a signal sequence is conferred from a very short first exon and the catalytic domain is encoded by the much longer second exon. This pattern is conserved in the close homolog present in MDV-2 HPRS-24 (22). Remarkably, aside from the MDV-2 homolog, the closest homologs to v-LIP are ORFs from several avian and fowl adenoviruses (GenBank accession nos.…”
Section: Resultsmentioning
confidence: 95%
“…Both the repeat and the UL͞RL junction regions also show significant divergence among the different serotypes of MDV, underscoring the potential importance of these MDV-specific ORFs in conferring the oncogenicity of the viruses (GenBank accession no. AB024414) (21,22). In the ensuing sections, we will first describe MDV genes that have homologs in HSV-1, followed by a more detailed discussion of MDV-specific ORFs.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the UL28 gene product in HSV-1, together with those from UL6, UL25, UL32 and UL33, are required for full capsid formation, viral DNA packaging, and viral glycoprotein expression on the surface of virus-infected cells (Addison et al, 1990;Tengelsen et al, 1993). Alignment analysis indicated that the predicted nuclear localization sequence, RRK, of UL28 protein in DEV clone-03 was conserved among the herpesviruses (Kato et al, 1999), which suggested that DEV UL28 protein may be related to the capsidation of virus.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted amino acid sequence of the ORF at 13735 to 10877 bears herpesvirus single-stranded DNA binding protein homology, with 29 to 34% identity and 46 to 51% similarity to the model alphaherpesviruses (Table 2). This homology includes a putative conserved zinc finger motif at predicted positions 491 to 502 (CDLCDVETRHVC; Zn finger consensus sequence is C-X 2-5 -C-X 2-15 -C/H-X 2-4 -C/H, where bold indicates conserved residues) (11), followed by a putative conserved DNA binding domain (R 795 AEKVMQLQPILNGPHGYLLKRFHERLFPTN KAIS AMAFWNRAQNNK; the U L 29 DNA binding consensus motif is K/R-X 2-3 -K/R-X 9-10 -F-X 4 -F-X 1-3 -K/R-X 10-12 -W-X 6 -R (16). The U L 29 nucleotide sequence reported here is Ͼ99% identical to a FPTHV U L 29 sequence in GenBank (27).…”
Section: Sequence Analysis Of Hawaiian Green Turtle Fpthvmentioning
confidence: 99%